Low vector competence in sylvatic mosquitoes limits Zika virus to initiate an enzootic cycle in South America - Fernandes, Rosilainy S. (Sci Rep, 2019)
Zika virus (ZIKV) has spread in the Americas since 2015 and the potential establishment of a sylvatic transmission cycle in the continent has been hypothesized. We evaluated vector competence of five sylvatic Neotropical mosquito species to two ZIKV isolates. Distinct batches of Haemagogus leucoceleanus, Sabethes albiprivus, Sabethes identicus, Aedes terrens and Aedes scapularis females were respectively orally challenged and inoculated intrathoracically with ZIKV. Orally challenged mosquitoes were refractory or exhibited low infection rates. Viral dissemination was detected only in Hg. leucocelaenus, but with very low rates. Virus was not detected in saliva of any mosquito orally challenged with ZIKV, regardless of viral isolate and incubation time. When intrathoracically injected, ZIKV disseminated in high rates in Hg. leucocelaenus, Sa. identicus and Sa. albpiprivus, but low transmission was detected in these species; very low dissemination and no transmission was detected in Ae. terrens and Ae. scapularis. Together these results suggest that genetically determined tissue barriers, especially in the midgut, play a vital role in inhibiting ZIKV for transmission in the tested sylvatic mosquito species. Thus, an independent enzootic transmission cycle for ZIKV in South America is very unlikely.